High-flux positron generation via the ultra-intense laser irradiating density-modulated plasmas - Liu, Jian-Xun; Gao, Ting; Wang, Xu; Jin, Hong-Bin; Deng, Wei-Qiang; Liu, Tai-Yang; Yu, Tong-Pu (Frontiers in Physics, 2023)
To investigate plasma density during the Breit–Wheeler positron generation, a comparative study of four plasma targets is performed via the PIC (particle-in-cell) code EPOCH. When an ultra-intense laser (2.8×1023 Wcm−2) is incident, more positrons with high energy are generated in the increasing density plasmas. The positron yield is already 1.5×108 with a cutoff energy of 2 GeV at t=37T0. It is demonstrated that increasing density plasmas will enhance gamma photon radiation and positron generation. In increasing density plasmas, under-dense plasmas favor electron acceleration, and over-dense plasmas will induce laser reflection. Cross sections of the Compton back-scattering and the BW positron generation are both increased via high-energy electrons colliding with the reflected laser. In addition, increasing the laser intensity will directly enhance positron generation. This investigation will further facilitate high-flux positron generation and application.